Visitors’ satisfaction and development strategy of agrotourism: evidence from Semarang, Indonesia - Raras Sekar Kinasih; Wiludjeng Roessali; Edy Prasetyo (Publisher of Widyagama University of Malang (UWG Press), 2020)
Visitor satisfaction is fascinating to learn because this is always a significant positioning in developing tourism destination.This study aims to analyze visitor satisfaction and formulate the agrotourism development strategy. The research survey was conducted in Purwosari Agrotourism, Mijen District, Semarang City, Indonesia. A total of 100 visitors and 20 people were purposively selected to address research objective. Visitor satisfaction is evaluated using the 7P marketing mix approach. The analysis method uses the Importance Performance Analysis and Customer Satisfaction Index to analyze visitor satisfaction; and Strength, Weakness, Opportunity, and Threat (SWOT) analysis to formulate development strategy. The results showed the location, transportation, promotion, and physical evidence (parking area, toilets, and information boards) are the main priority attributes of improvement. The response of visitors was in the satisfied category with a total Satisfaction Index of 73.39%. The development strategy of Purwosari Agrotourism shows the SO (strength and opportunity) strategy approach, which means being in a favorable position with aggressive strategy recommendations. The strategy includes the innovation of tourism products, collaboration with other tourism objects to create tour packages, and expand product marketing networks.JEL Classification: Q13; R58; Z32